The attorney-client relationship and professional honorability - Cooper, H. H. A. (1968)
The author aims to address the question of whether law is an honorable profession by analyzing the relationship between lawyer and client and the moral dilemmas that lawyers may face in the exercise of their profession. In this context, it addresses three difficult scenarios that may arise in the course of a career: (i) Can the lawyer discredit a witness who is telling the truth? (ii) Can the lawyer offer a witness who is lying? (iii) Can the lawyer defend a client whom the lawyer knows is guilty? While recognizing the importance of loyalty and confidentiality between the lawyer and his client, it is emphasized that lawyers are primarily responsible to the law and the judiciary. In this regard, the author notes that lawyers have a duty to their clients, but that duty is subordinate to a higher duty associated with the proper administration of justice, respect for the law, and the truth.